2015
DOI: 10.1039/c4cp04128c
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic investigation of morphology evolution in P3HT–PCBM films induced by liquid crystalline molecules under external electric field

Abstract: We demonstrate that the morphology of poly(3-hexyl thiophene) and [6,6]-phenyl-C61-butyric acid methyl ester (P3HT-PCBM) bulk heterojunctions (BHJ) could be tuned by the 4-cyano-4'-pentylterphenyl (5CT) liquid crystalline molecules under electric field assisted treatment for enhanced solar cell performance. The miscibility and interactions between the components were carefully studied, showing that 5CT could induce the crystallization of P3HT to form edge-on structures in ternary blends after electric field as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…Some of the nonvolatile small molecule additives were used to control the horizontal and vertical phase separation. [262][263][264][265][266][267][268][269][270][271][272][273][274][275][276] As some representative examples, Kim et al 262 employed a fractional amount of nonvolatile additives (a) in P3HT/PC 61 BM blend and the PCE was improved. This additive selectively partitioned into P3HT due to its special hydrophobicity, and effectively enhanced phase separation between the electron donor and acceptor phases.…”
Section: Donor/nonvolatile Small Molecule Additive/acceptormentioning
confidence: 99%
“…Some of the nonvolatile small molecule additives were used to control the horizontal and vertical phase separation. [262][263][264][265][266][267][268][269][270][271][272][273][274][275][276] As some representative examples, Kim et al 262 employed a fractional amount of nonvolatile additives (a) in P3HT/PC 61 BM blend and the PCE was improved. This additive selectively partitioned into P3HT due to its special hydrophobicity, and effectively enhanced phase separation between the electron donor and acceptor phases.…”
Section: Donor/nonvolatile Small Molecule Additive/acceptormentioning
confidence: 99%
“…The (100), (200), and (300) peaks positions are associated with the out-of-plane and the dominant peak in the in-plane was the (010). Prior work 29,[31][32][33][34][35] has shown that P3HT chains preferentially align themselves in the edge-on configuration with the p-p stacking in the (010) direction. Therefore, with the application of pressure in the out-of-plane direction and perpendicular to the substrate, the bonds between the polymer backbones are also elongated in the in-plane direction leading to the edgeon configuration.…”
Section: Resultsmentioning
confidence: 99%
“…A thiophene-containing small molecule has been found to act as a nucleating agent to improve the conformation of polymer chains and enhance their crystallinity. 49 Accordingly, we conclude that BDT6T, a small molecule containing thiophene units, could function as a morphology controller, inducing a favorable active layer morphology with interpenetrating nanoscale domains. Figure S5 shows AFM images (tapping mode) with higher resolution for different conditions.…”
Section: ■ Experimental Sectionmentioning
confidence: 98%